PENGARUH MEDIA CETAK TERHADAP KEMAMPUAN MENULIS KARANGAN ARGUMENTASI - Gultom, Candra R (EDUKASI KULTURA JURNAL BAHASA SASTRA DAN BUDAYA, 2015)
This study aims to describe the influence of newspaper print media on the ability to write essays argumentation class X SMA Santa Lucia learning year 2012/2013. The population of this research is all class X SMA Santa Lucia Sei Rotan consisting of four classes with a population of 130 students. Of the number of students was assigned a sample that is 64 people. The method used is an experimental method that compares two groups, given learning to write essays arguing with print media newspapers or experimental class (X) and the group learning with print media textbook or classroom control given different treatment. Experimental class data captured argument essay writing essay test using compiled for the goals to be achieved. Prior to the analysis of data, analysis persayratan test is a test of normality and homogeneity tests. Distribution data obtained: the experimental class has an average of 79.34 with a standard deviation of 6.72 and a control class has an average of 67.31 and a standard deviation of 8.07. The results of the normality test calculations obtained: an experimental class to obtain price Lo (Lhitung) = 0.13 and Lt (Ltabel) = 0.15. Turns Lhitung <Ltabel or 0.13 <0.15 which argument essay writing using print media newspapers normal distribution; and gain control class price Lo (Lhitung) = 0.07 and Lt (Ltabel) = 0.15. Turns Lhitung <Ltabel or 0.07 <0.15. It is proved that the learning outcome data write essays arguing with print media textbook normal distribution. The results of the combined variance homogeneity test calculations studied two groups obtained X2hitung = 1.42 and X2tabel = 1.84. Price X2hitung <X2tabel namely 1.42 <1.84. Hypothesis testing is done mendengan using 't' test. From the calculation hypothesis test obtained t = 6.39 ttabel further consultation with the significance level of 5% with df = (N1 + N2) - 2 = 60. In the table t with df = 60 obtained ttable significance level of 5% = 2.00. Testing criteria states that Ha accepted if t count> t table (6.39> 2.00), then the alternative hypothesis is accepted that states the newspaper print media better than the print media by increasing the letter textbook writing essays argument proceeds learn some vital lessons. Keywords : Media Print, Write essays argumentation